2016
DOI: 10.1037/ort0000101
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress symptoms in context: Examining trauma responses to violent exposures and homicide death among Black males in urban neighborhoods.

Abstract: Concentrated disadvantage in urban communities places young Black men at disproportionate risk for exposure to violence and trauma. Homicide, a health disparity, positions Black males vulnerable to premature violent death and traumatic loss, particularly when peers are murdered. Posttraumatic stress disorder (PTSD) has been demonstrated as a health consequence for middle-income and White homicide survivors; however, understandings of traumatic stress among young Black men situated in contexts of chronic violen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 59 publications
11
84
2
Order By: Relevance
“…For example, ECV is associated with alterations in salivary cortisol responses (Aiyer, Heinze, Miller, Stoddard, & Zimmerman, 2014;Kliewer, 2016;Peckins, Dockray, Eckenrode, Heaton, & Susman, 2012;Suglia, Staudenmayer, Cohen, & Wright, 2010) and more self-reported hyperarousal symptoms (Fowler et al, 2009;Margolin & Gordis, 2000;Mazza & Reynolds, 1999;Paxton, Robinson, Shah, & Schoeny, 2004;Singer, Anglin, Song, & Lunghofer, 1995) in African American adolescents. Further, the most commonly experienced symptom of PTSD in young adult African American men is physiological hyperararousal, exhibited in direct response to the threat of community violence (Rich & Grey, 2005;Smith & Patton, 2016).…”
Section: An Alternate Model Of Reactivity To Ecvmentioning
confidence: 99%
“…For example, ECV is associated with alterations in salivary cortisol responses (Aiyer, Heinze, Miller, Stoddard, & Zimmerman, 2014;Kliewer, 2016;Peckins, Dockray, Eckenrode, Heaton, & Susman, 2012;Suglia, Staudenmayer, Cohen, & Wright, 2010) and more self-reported hyperarousal symptoms (Fowler et al, 2009;Margolin & Gordis, 2000;Mazza & Reynolds, 1999;Paxton, Robinson, Shah, & Schoeny, 2004;Singer, Anglin, Song, & Lunghofer, 1995) in African American adolescents. Further, the most commonly experienced symptom of PTSD in young adult African American men is physiological hyperararousal, exhibited in direct response to the threat of community violence (Rich & Grey, 2005;Smith & Patton, 2016).…”
Section: An Alternate Model Of Reactivity To Ecvmentioning
confidence: 99%
“…This suggests that more universal antisocial features not specific to a street code are also driving violent responses to interpersonal affronts and disputes. In a qualitative study of young, African American males who were co-victims of homicide, [31] reported high prevalence of Posttraumatic Stress Disorder (PTSD) symptoms, including acute stressors (100% prevalence), intrusion/thought intrusion (46% prevalence), avoidance (46% prevalence), negative alterations in cognition and mood (65%), and alterations in arousal and reactivity/hypervigilance (68%). Although code of the street normative valuations were present in their data, their study reveals that exposure to acute levels of crime, disorder, and violence works to cultivate a psychological state where violence is often potentiated.…”
Section: The Code Of the Street And Psychological Factorsmentioning
confidence: 99%
“…Studies have consistently found a relationship between exposure to violence in the neighborhood and poorer mental health [12][13][14]. In a qualitative systematic review of the literature on high-risk urban neighborhoods and exposure to violence, authors found that young African-American men had higher rates of depression and psychological distress, but called for more research on the specific variables and pathways in those neighborhoods that predict poor mental health [12].…”
Section: Experience Of African-american Youth In Violent Neighborhoodsmentioning
confidence: 99%
“…In a qualitative systematic review of the literature on high-risk urban neighborhoods and exposure to violence, authors found that young African-American men had higher rates of depression and psychological distress, but called for more research on the specific variables and pathways in those neighborhoods that predict poor mental health [12]. Smith conducted a qualitative study of the symptoms of post-traumatic stress disorder (PTSD) discussed by young, African-American men who have lost a loved one to homicide, and found that more than 70% of those youth identified symptoms of PTSD, and most frequently, the need to be on point or hypervigilant [13]. Additionally, in a quantitative study of Black youth, Assari found that adolescent African-American males who reported living in unsafe neighborhoods were at greater risk for major depressive disorder (MDD) than African-American females and Caribbean Black males and females [14].…”
Section: Experience Of African-american Youth In Violent Neighborhoodsmentioning
confidence: 99%